Age-related changes in corneal thickness and endothelial characteristics - Galgauskas, Saulius (Dove Medical Press, 2013)
PURPOSE: To determine the influence of age on central corneal thickness (CCT), endothelial cell density (ECD), average cell size, coefficient of variation in cell size, and percentage of regular hexagonal cells; and to estimate the average ECD and CCT in seven age groups. MATERIALS AND METHODS: After obtaining informed consent, 211 Caucasian patients (358 eyes) were examined using a noncontact specular microscope at the Center of Eye Diseases in Vilnius University Hospital Santariskiu Clinic. The main corneal parameters were: ECD, average cell size, coefficient of variation in cell size, percentage of regular hexagonal cells, and CCT. Subjects (20–89 years) were stratified by age into seven groups. Correlations between CCT, endothelial parameters (ECD, percentage of regular hexagonal cells, average, coefficient of variation), and age were found. Student’s t-test and Pearson’s correlation coefficient (r) values were calculated. RESULTS: A total of 114 (54.03%) women and 97 (45.97%) men participated in the study. Average ECD (cell/mm(2)) ranged from 2,931 (±371) in 20–29 year olds to 2,222 (±182) in 80–89 year olds; CCT (μm) ranged from 563 (±44) in 20–29 year olds to 540 (±35) in 80–89 year olds. A strong inverse correlation was observed between age and corneal ECD (r=−0.650, P<0.01) and a weak inverse correlation was observed between age and CCT (r=−0.156, P<0.01). ECD and CCT correlated directly (r=0.232, P<0.01). The average size of corneal endothelial cells directly correlated with age (r=0.586, P<0.01). There was no correlation between age and the coefficient of variation in cell size nor the percentage of regular hexagonal cells (P>0.05). CONCLUSION: Young people have higher ECD. CCT also decreases, but its dependence on age is weaker. A lower cell density indicates a thinner cornea. The variation in cell size and percentage of regular hexagonal cells are not dependent on age.